EFFECT OF PRO-OXIDANT ADDITIVES ON DEGRADATION OF MULCH FILM BASED ON RECYCLED POLYETHYLENE - Khoi, Nguyen Van; Tuan, Le Quang; Thang, Tran Vu; Manh, Nguyen Van; Phuong, Hoang Thi; Trang, Pham Thi Thu; Hoan, Đỗ Công; Cong, Trinh Duc (Vietnam Journal of Science and Technology, 2015)
The effect of pro-oxidant additives (Iron, Cobalt and Manganese stearates) on the biodegradation of recycle polyethelene mulching films was studied in both accelerated weather and natural exposure conditions. The degradation degree of film was determined by measuring mechanical properties and scanning electronic microscope (SEM). The results showed that the mechanical properties of film samples with pro-oxirant additives decreased rapidly, and that surface film with additives was degraded clearly compared to the films without additives after 30 cycles of accelerated weather. Reliability in terms of acceleration are 28 - 30 cycles of exposure and in the natural conditions reached 10-12 months.